LEGAL RESPONSIBILITY OF BUILDING OWNERS TOWARDS FIRE VICTIMS: A CIVIL LAW PERSPECTIVE - Suhermi; Windarto; Oktaviani, Firya (Leges Privatae, 2024)
Fire is a disaster that is often caused by the negligence of building owners in meeting the required safety standards, threatening both property and human lives. This study aims to evaluate the legal responsibility of building owners within the civil law system, particularly regarding negligence that leads to physical and material losses. The research is conducted using a normative juridical method, focusing on the analysis of relevant regulations, such as Law No. 28 of 2002 on Building Construction, Law No. 24 of 2007 on Disaster Management, and provisions in the Civil Code (KUHPerdata), especially Article 1365.  The research findings indicate that, although existing regulations have outlined the obligations of building owners to prevent fires, the implementation faces various challenges. These challenges include insufficient supervision, suboptimal law enforcement, and lengthy legal processes for victims to obtain justice. The study identifies a gap between legal norms and field practices, resulting in the difficulty of enforcing building owners' responsibilities. Through this study, it is hoped that solutions can be found to strengthen the civil law system, ensuring that building owners are held more accountable and fire prevention efforts are effectively implemented, providing optimal protection for building occupants and users.